PENGARUH KEBIJAKAN PERDAGANGAN TERHADAP NILAI EKSPOR PRODUK PERTANIAN: STUDI LITERATUR DI INDONESIA - Loso Judijanto (CV. ADIBA AISHA AMIRA, 2025)
This study aims to analyse the impact of trade policies on the value of Indonesian agricultural exports through a literature review of various academic sources and government policies. The findings reveal that trade policies, including tariffs, non-tariff measures, and market liberalisation, significantly impact the performance of agricultural exports. Appropriate policies can enhance the competitiveness and market access of Indonesian agricultural products at the global level, while challenges such as overlapping regulations, high logistics costs, and stringent international standards remain key obstacles. This study also highlights the importance of synergy between trade policies, infrastructure development, technological innovation, and human resource development to drive sustainable growth in agricultural exports. In conclusion, the optimisation of adaptive and integrated trade policies is essential to enhance the value of Indonesia's agricultural exports in international markets.